THE DIFFERENCES DECLINE BREAST ENGORGEMENT CONDUCTED CONVENTIONAL METHODS (BREAST MASSAGE) WITH HERB YEAST-KATU - Susilawati Susilawati; I Gusti Ayu Karnasih; M. Wildan (UPT Penerbitan Universitas Jember)
In the nation's development, improving thequality of human beings should be initiated asearly as possible that early on that since I was ababy, one factor that plays an important role inimproving the quality of human beings arebreastfeeding (breast milk). Breastfeeding aspossible is an important activity in themaintenance of children and the preparation offuture generations in the future. It is estimatedthat 80% of mothers who gave birth were able toproduce milk in sufficient quantities for thepurposes of the baby in full without extra foodduring the first six months, women with poornutrition can produce enough milk without anyadditional food during the first three months(Depkes, 2009)Many studies have examined the benefits ofbreastfeeding exclusively in terms of loweringinfant mortality, lower infant morbidity, optimizepartumbuhan baby, helping the development ofchildren's intelligence, and help extend thedistance of the pregnancy for the mother. InIndonesia, the Ministry of Health of the Republicof Indonesia through community nutritionimprovement program has been targetingcoverage of 6 months of exclusive breastfeedingat 80% (Depkes, 2009). However, this figure isvery difficult to achieve even the prevalence ofexclusive breastfeeding trends from year to yearcontinues to decline. According to (WHO, 2002)Five out of ten women (50%) who arebreastfeeding, when the late breast-feeding theirbabies breast milk there will be a dam, so a lot ofthe milk glands swollen that contain milk that hasnot been issued (Sarwono, 2002)Breast swelling is the buildup of breast milk in thebreast caused by breast milk is not excluded tothe maximum , causing stasis breast milk. Stasisso that the mother's milk stored inside the breast(Manuaba , 2008)Occlusion of breast milk can cause breast painand during feeding and can increase bodytemperature. Handling the dam breast milk isdone by conventional treatments is throughmassaging the breast to remove the dam , butmassage is rarely implemented due cause painMadurese communities have a culture in thetreatment of breast engorgement is to provideherb Katu and yeast . Giving herb Katu and yeastbecome mothers suckle choice because it servesto free breast swelling and provide comfort to thebreast when compressing . It can also reducebreast pain and cold.The content of papaverine ( Soka , 2003) and thecontent of antipyretic and analgesic ( Lee , 1996)in the leaf valve reduce pain and heat as a resultof engorgement. While the yeast fermentationprocess heat effects . Effect of heat yeaststimulates vasodilatation of blood vessels andducts that facilitate the ducts.PurposeAnalyze the Difference Between Breastengorgement Decrease Breast Caremassage(conventional) And The given Herb Katu-YeastAnalyzing the differences decrease breastengorgement given conventional treatment andwere given the herb Katu-YeastIdentifying decline in women after breast swellingdo massage treatments ( conventional)Identifying decrease breast engorgement inmothers after the Katu - given herb leaves YeastAnalyzing the difference in the reduction in breastswelling performed with massage treatments (conventional ) and given Herb Katu-YeastBenefitDevelopment of Science and Technology obstetriccare, especially maternal and child healthinterventions with local culture basedImproving the quality of obstetric care, especiallyin the care duringchildbirthHelping mothers breastfeed in addressing thebreast engorgement, using local cultural wisdom